Kindstod und Kindstötung - Häßler, Frank; Schepker, Renate; Schläfke, Detlef (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2007)
Violence against children can take many forms of physical and psychological violence or neglect. The killing represents the culmination of the violence or the result of a psychological disorder of the perpetrator. The media report child killings with frightening regularity. The cases not only cause nationwide concern, but also raise questions about causes and effective preventive protective measures. For Germany, 1-2% child deaths among homicides can be assumed. Due to the complexity of the problems underlying the phenomenon, however, a high number of unreported cases can be assumed, since even "sudden child death" can hide hidden anticides and a "Munchausen syndrome by proxy" can end with accidental or even intended child death. This book covers the phenomenon of child death and child killing from the perspective of forensic psychiatrists, pediatrists, forensic doctors and lawyers. Based on historical considerations, the experts use examinations and individual cases to show specifics that are of great importance in everyday medical and legal practice and that are brought together for the first time in this current and comprehensive form.